Ethnography and Bush Kinder Research: A Review of the Literature. Issue 3 (September 2021) - Speldewinde, Christopher; Kilderry, Anna; Campbell, Coral
Bush kindergarten programmes (known as bush kinders), where preschool children learn in, about and with nature, are proliferating in Australian early childhood education. This scoping review reports on, and analyses, the research literature pertaining to how ethnography has been applied to the bush kinder context. We included studies conducted in related contexts, such as forest schools, and other programmes that focus on nature pedagogy, as these contexts assist us to better understand bush kinders. The findings from our literature review illustrate and confirm that empirical research in bush kinder settings is in its early stages. Consequently, bush kinders present opportunities for piloting research methodologies. After a review of the research literature, it was found that ethnography as a research methodology is valuable to understand teacher pedagogy, young children's learning, the implications of researcher positionality, the context and the place of bush kinders in early childhood education and care.